Vehicles for the North - Velikanov,D.; Levin,A. (1973)
Siberian conditions require sepcial modifications for standard-model trucks and buses. A series of 'northern duty' vehicles are now available. They incorporate additional insulation and better heaters to protect driver and passengers, special equipment to facilitate engine warm-up and tires, and other rubber components of cold-resistant rubbers which retain their elasticity down to -60C. The current 5-year plan projects the delivery of 14 thousand such vehicles. Their special operation and maintenance requirements will demand additional training of drivers and mechanics. Trans. of Za Rulem (USSR) n12 p14-15 1972, by Markowitz.